Valoração e responsividade em questões do Exame Nacional do Ensino Médio nos anos 2019 e 2020 - Guedes, Karol Costa (2021)
This doctoral thesis, supported by the dialogic conception of language, consists of an exploratory, bibliographical and qualitative survey, inspired by the following problem-question: “How is the valuation and responsiveness of the developing author presented in the genre of Enem's question?”. To answer this question, its objectives were organized as: General – to investigate the author's valuation and responsiveness shown in Enem's question genre, through dialogical relations, as a characteristic of the exam; and Specific – check the discursive sayings in the documents that parameterize the functioning of Enem, known as reference matrices and annexes relating to the objects of knowledge associated with them; analyze Enem's question as a discursive genre; examine how the text(s) that structurally compose the first element of the Enem questions are valued; verify the dialogical relationships through which the author elaborates the questions; and analyze the responsiveness and valuation of the Enem issue. Methodologically, analysis of documents and ten questions from Enem (2019 and 2020) were carefully selected, which dialogued exemplary with concepts, notions and ideas from the theoretical chapters, by sequencing a kind of three steps: 1) visualization of the question and attention to the first element of the question genre (the textual fragment, the refraction of the genre used in the question and the way in which the author values this first element, through linguistic and textual marks); 2) identification of the dialogical relationship present in the second and third elements of the question (statement and alternatives) through which the writer produces his valuation and responsiveness to the cut text and the Enem reference matrix; and 3) discussion about the author's valuation and responsiveness present in the question. Finally, when analyzing the enunciation that constitutes the Enem reference matrices and the knowledge objects associated with them, it was possible to verify the expressive and thematic direction that intends the evaluation process of the exam, based on what the Enem considers as an evaluation contextualized and interdisciplinary, through the author's appreciative accent on socially situated cognitive know-how. Furthermore, by analyzing the question of Enem as a discursive genre, we reflected on the pedagogical influence that this exam promotes in the evaluation processes of elementary education school institutions, since the compositional form, style and theme are strongly demarcated in the aim to develop an evaluative process that follows a discursive order that relates to the contextual, situational, non-technical and non-mechanistic purpose of measuring knowledge. The axiological positions demarcated by textual clipping/fragmentation/refraction and linguistic-textual choices that offer a certain semantic weight to the whole issue reveal the constitution of Enem as an evaluation event that is established by the validation of the evaluation process, which, in its realization , it is subjective, argumentative, dialogic and responsive – a significant historical mark of the exam, which validates an entire evaluation process in the Brazilian educational system regarding the identification and responsive-active understanding of objects of knowledge translated into skills and abilities dear to the constitution of the image of an ideal candidate subject to enter higher education.